Exploring geochemical assessment and spatial distribution of heavy metals in soils of Southern KP, Pakistan: employing multivariate analysis. Issue 17 (23rd December 2022) - Ali, Iftikhar; Khan, Imdad Ullah; Khan, Muhammad Jamil; Sardar, Tariq; Deeba, Farah; Hussain, Haziq; Ullah, Kalim; Khan, Qudrat Ullah; Khan, Mumtaz; Khan, Muhammad Daud
ABSTRACT: Soil pollution with heavy metals is continuously expanding with the rapid development of industrialisation and agriculture. The current study was aimed to determine the skewed nature and spatial distribution of soil heavy metals pollution in southern areas of Khyber Pakhtunkhawa. Fifty four soil samples were collected from the selected sites in southern districts and analysed for various soil physico-chemical and elemental concentrations. Various metals content, i.e. (Pb, Cd, Ni, Cr) was determined after acid digested through atomic absorption spectrophotometry. Results of the metals content in soil samples showed maximum values Pb (46.38), Cd(6.74), Ni(45.58), Cr(58.08) mg/kg, bluk density 1.46 g/cm 3 and lowest pH value 6.53 for Lakki cement factory (LCF) site. Other parameters like soil electrical conductivity, total dissolved solids, percent porosity and soil urease activity also indicated higher values, i.e. 504 µs/cm, 250 mg/lit, 66% and 440.50 respectively. Positive Pearson correlation was found between metals concentration and soil physico-chemical properties except percent porosity and bulk density exhibited negative correlation. The multivariate statistical analysis of the data formed principal component that accounted for a total variance of 71.1%, on the basis of which metal contamination is traced to both geogenic and anthropogenic sources. Spatial distribution of the metals concentration showed higher concentration of Cd, Cr, Ni in Lakki cement factory (LCF) soil except Pb content that was observed maximum in Indus highway Karak (IHK) soil samples. Geoamccumulation index (Igeo ) of the samples sites showed moderate contamination for studied metals with some uncontaminated sites showing a value of Igeo > 0. The study concludes a baseline data for metals concentration in the area, which can be used as a beacon for various strategic plannings regarding soil resource management in order to address the metals related health issues and environmental pollution.